0263 Slow-wave Disruption Improves Irritability in Males with Major Depression: Potential Implications for Understanding the Impact of Sex Differences on Sleep and Neuroplasticity. (25th May 2022) - Goldschmied, Jennifer; Goldstein, Elena; Palermo, Emma; Costello, Samantha; Games, Margaux; Gehrman, Philip
Abstract: Introduction: Irritability has been proposed to be a core symptom of male-specific major depressive disorder (MDD), with a greater propensity to experiencing anger attacks and overreacting to minor annoyances compared to females with MDD. Males with MDD have also been shown to exhibit a pattern of reduced slow-wave sleep (SWS) that is not characteristic of females. Because SWS has been implicated in the homeostatic regulation of neuroplasticity, it is possible that this mood dysfunction in males is a result of SWS alterations via impairments in neuroplasticity. Therefore, in this study we aimed to manipulate SWS and examine its impact on mood. Methods: 19 individuals (11 F) with MDD were recruited for an ongoing clinical trial. Participants spent two nights in the sleep laboratory one week apart: a baseline (BL) night, and a night of slow-wave sleep disruption (SWD) utilizing auditory stimulation. Irritability was assessed in the morning following each overnight visit using the 5-item Brief Irritability Test (BITe). Repeated measures ANOVA was used to evaluate the change in irritability following SWD with condition (BL, SWD) as the within-subject factor and sex (M, F) as the between-subjects factor. Results: Results revealed a significant Condition x Sex interaction (F(1, 17) =10.1, p=.006) for change in irritability scores, with post-hoc t-tests indicating that males with MDD showed a significant decrease in irritability following SWD, t(7)=2.22, p<.05 while women showed a significant increase in irritability, t(10)=-2.34, p<.05. Changes in irritability were not found to be associated with changes in N3. Conclusion: These data demonstrate that experimentally reducing SWS decreases irritability, a core symptom of mood dysfunction, in males with MDD. As SWS has been theorized to facilitate synaptic downscaling, these results may indicate that maintaining waking levels of synaptic strength in males improves depressive symptomatology and may point to the importance of sex differences in sleep and psychopathology. Moreover, these results suggest that the modulation of neuroplasticity via sleep manipulation may be a potential therapeutic target. Support (If Any): K23MH118580 (JG)